Building School Connectedness Through Structured Recreation During School: A Concurrent Mixed‐Methods Study. - Wilson, Kylie; Ramella, Kelly; Poulos, Allison (Journal of School Health, 2022)
BACKGROUND: School connectedness (SC) is associated with improved health and academic outcomes. The purposes of this study were to explore factors contributing to students' perceptions of SC and if participation in structured recreation at school was associated with SC. METHODS: We used concurrent mixed‐methods including cross‐sectional qualitative data to explore factors contributing to SC among fifth‐ and sixth‐grade students at 2 schools in Phoenix, AZ, USA (N = 330), and quantitative measures to explore the association between SC and recreation participation (N = 129). Students completed a journaling activity to identify factors contributing to feelings of SC. Responses were analyzed using both deductive and inductive approaches. Student surveys were analyzed using 1‐way analyses of variance to assess differences between participation level and SC. RESULTS: Eight themes contributing to SC emerged: Relationships (peer, adult), Competence (competence), Autonomy (choice), Relax (relax), Recreation (structured, play), Fun (fun), Academics (academic learning), and Environment (food and safety). Participation in structured recreation programming in the classroom and at recess were associated with higher levels of SC (p <.05). CONCLUSIONS: School practitioners can integrate opportunities for structured recreation in the classroom and at recess as a fun and engaging strategy to foster adult support and peer relationships, enhancing SC.